Pannexin1 channels in the liver: an open enemy - Van Campenhout, Raf; Caufriez, Anne; Tabernilla, Andrés; Maerten, Amy; De Boever, Sybren; Sanz-Serrano, Julen; Kadam, Prashant; Vinken, Mathieu (Frontiers in Cell and Developmental Biology, 2023)
Pannexin1 proteins form communication channels at the cell plasma membrane surface, which allow the transfer of small molecules and ions between the intracellular compartment and extracellular environment. In this way, pannexin1 channels play an important role in various cellular processes and diseases. Indeed, a plethora of human pathologies is associated with the activation of pannexin1 channels. The present paper reviews and summarizes the structure, life cycle, regulation and (patho)physiological roles of pannexin1 channels, with a particular focus on the relevance of pannexin1 channels in liver diseases.